Impacto de atividades lúdicas no processo de adaptação de crianças com câncer em cuidado paliativo: à luz da teoria adaptativa de Callista Roy - Pereira, Jéssica Barreto (2019)
Children with câncer in palliative care go through long hospital stays. The nursing team seeks to create strategies to help children in care, such as ludic activities and the nursing theories. The present dissertation consists of two articles, the first one is titled: Application of Callista Roy's Theory of Adaptation in Pediatrics: an integrative review. Aim: to investigate in the scientific publications released in national and international scope, the application of the Theory of Adaptation of Callista Roy in the pediatric practice. Methodology: Integrative literature review, from 1998 to 2018. It was based on LILACS, PubMed, MEDLINE, IBECS, BDENF, CINAHL, SCOPUS and Scielo digital library. Results: 10 (ten) articles were identified addressing the application of the Theory of Adaptation in Pediatrics. Conclusion: The application of the Theory in Pediatrics positively stimulates the adaptation of the patient to the new. The second article is entitled: The Ludic In The Adaptation Of Children With Cancer Under Palliative Care, based on Roy's model. Aim: To analyze the impact of ludic activity in children with cancer under palliative care based on Callista Roy's Theory. Methodology: It is a descriptive, observational and interventional study of qualitative nature based on the Adaptive Theory proposed by Callista Roy (1977). Ten children aged 6 to 12 years with cancer in palliative care attended the outpatient clinic of the philanthropic hospital in the city of João Pessoa-PB. The research was approved by the Ethics and Research Committee with CAE: 82946618.9.0000.5188. Results: It was divided into two categories: Application Of The Callista Roy Adaptation Model according to the modes and stimulus, and ludic intervention as a strategy of the nursing process. Conclusion: the ludic activity has a positive and essential impact on the adaptation of the child with cancer under palliative care in the hospital context.